Conversor MPPT de estágio único conectado à rede elétrica baseado no conversor de capacitor flutuante - Muller, Guilherme David (2023)
Considering the current trend of growth of systems based on renewable energy sources, mainly photovoltaic distributed generation (DG’s), new topologies of DC-AC converters are being developed for conversion systems with a focus on multilevel converter structures, in order to increase efficiency at the lowest possible cost. This work describes a literature review on photovoltaic energy processing, including the operation of the solar system, MPPT methods, types of converters used and modulation strategies. After the review, a new grid-connected single-stage DC-AC inverter topology is presented, inspired by the flying capacitor multilevel converter cell. All components of the proposed converter were dimensioned and, for validation, a simulation structure was developed using the MPPT control through the incremental conductance algorithm acting only on the modulating signal angle, with unit modulation index. As a modulation strategy, PWM modulation with two phase shifted carriers (PS-PWM) was used. The system was simulated in the MATLAB®/Simulink environment for a 6.4 kW photovoltaic system at 25 ◦C and subjected to changes in irradiance to analyze the behavior and performance of the converter.